Pemantauan Kualitas Udara Berbasis Internet Of Things - Alvino Octaviano; Sofa Sofiana; Dion Orlando Agustino; Perani Rosyani (KLIK: Kajian Ilmiah Informatika dan Komputer, 2022)
Air quality control is very important to do to avoid several diseases and minimize the effects of lung damage for Covid-19 survivors due to the increasing number of air pollution. This makes it quite difficult for people to know the air quality. The method used is a research and development method that includes system design, tool making, web-based application design, tool integration, and system testing. The sensors used are the MQ-7 sensor for CO gas, the Sharp GP2Y1010AU0F sensor for dust, and the DHT11 sensor for temperature and humidity. Each sensor is assembled into one with the WeMos D1 R2 microcontroller. The results of the system test for three days showed that the average temperature was 29.18°C, humidity was 80.01%, CO was 3983 g/m3 , and dust was 83.90 g/m3 . air quality monitoring systems for CO gas and dust pollutants can provide early warnings of poor air quality, so that people around the location of equipment placement can be more alert and reduce activities in the environment. Air quality data obtained from sensors can be displayed in real-time through the Blynk application and also stored on the ThingSpeak server which can be displayed on the ThingView application and web-based applications.